Analisis Yuridis Kontrak Pembiayaan Modal Ventura Dengan Pola Bagi Hasil Pada Pelaku Usaha Kecil dan Menengah - Indrajaya Indrajaya (Wajah Hukum, 2021)
In the business world, capital is an obstacle that is often faced by business actors, especially for small businesses. In order to solve this problem, the government issued regulations related to this problem. Among them through PP No. 9 of 2009 which regulates Financing Institutions and Minister of Finance Regulation No. 18/PMK.010/2012 Regarding Venture Capital Companies. In practice, this company in its capital participation with its business partner company is stated in the form of a written agreement (contract). The purpose of this study was to analyze the contents of the venture capital financing contract with a profit-sharing pattern at PT. South Sumatra SPV. Meanwhile, the problem of this research is how is the financing contract with the profit-sharing pattern applied by PMV with small and medium business actors in South Sumatra. This type of legal research is normative in nature, the legal materials used are primary, secondary and tertiary. It is carried out with a statutory approach and the conclusion of this research is that the financing contract carried out by the parties both formally and materially has fulfilled the legal requirements of a contract as regulated in Article 1320 and Article 1338 of the Civil Code Pdt and made before a Notary and signed by the business partner company and PMV represented by the management, namely the Board of Directors.